Sociodemographic factors related to the quality of life of patients with injuries in an outpatient clinic of a University Hospital (Research, Society and Development, 2022)
Objective: To identify the sociodemographic profile and quality of life of people treated at the wound clinic of a university hospital. Method: Cross-sectional, quantitative, exploratory and descriptive study with patients with wounds treated at an outpatient clinic. A questionnaire was used to collect sociodemographic characteristics and the WOUND QoL in Portuguese to assess quality of life. Results: 35 patients, most were men between 60 and 69, married, incomplete elementary education, monthly income of up to 2 minimum wages, retired, with arterial hypertension, sedentary and on continuous medication. As for quality of life, the variable female gender and sedentary lifestyle demonstrated a negative impact on quality of life, and the domain financial weight was the one with the lowest percentage. Conclusion: It is expected that this study can contribute with new knowledge, subsidizing new data to guide and adapt the care of patients with wounds, seeking to improve the quality of life.